2011
DOI: 10.1111/j.1523-5378.2011.00823.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Modified Concomitant Therapy for Helicobacter pylori Eradication in Turkey

Abstract: Although LAC plus tid metronidazole regimen achieved a much better eradication rate compared with the standard LAC regimen; this is the first study that has a relatively low success with a concomitant therapy. So in areas of high resistance like Turkey, one cannot expect a high success with any clarithromycin containing regimen and those should be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 15 publications
2
15
0
2
Order By: Relevance
“…However, several RCTs compared, in the same study and with the same protocol, two different durations of concomitant therapy, and demonstrated that the longer duration is more effective 215 218–220. Moreover, suboptimal results have been observed with a 5-day treatment duration in Latin America209 (73.5%) and South Korea (58.6%),221 but also in two studies of 14-day treatment from Turkey (75%)222 and South Korea (80.8%) 223. These inferior results have been attributed to the high prevalence of H. pylori strains resistant to clarithromycin and especially metronidazole in these populations 168 170.…”
Section: Working Group 3: Treatmentmentioning
confidence: 99%
“…However, several RCTs compared, in the same study and with the same protocol, two different durations of concomitant therapy, and demonstrated that the longer duration is more effective 215 218–220. Moreover, suboptimal results have been observed with a 5-day treatment duration in Latin America209 (73.5%) and South Korea (58.6%),221 but also in two studies of 14-day treatment from Turkey (75%)222 and South Korea (80.8%) 223. These inferior results have been attributed to the high prevalence of H. pylori strains resistant to clarithromycin and especially metronidazole in these populations 168 170.…”
Section: Working Group 3: Treatmentmentioning
confidence: 99%
“…A second outlier study was performed by Toros et al60 in Turkey, where only a 75% eradication rate was achieved despite the fact that high doses of metronidazole (500 mg three times daily) were used and a 14-day regimen was prescribed. It should be taken into consideration that, in Turkey, results with the standard triple therapy have also been far lower than expected.…”
Section: Efficacy Of the Concomitant Regimen For Eradication Of H Pymentioning
confidence: 99%
“…The poor performance of the quadruple, concomitant regimen here raises questions about whether this strategy can be a worthwhile one in an area of high clarithromycin resistance. In a further study, a levofloxacin-and rifaximin-based quadruple therapy was tested but found only to be equivalent to standard triple therapy in a Korean cohort [29].…”
Section: Nonbismuth-based Quadruple (Concomitant) Therapymentioning
confidence: 99%